Numerical Simulation of the Lubricant-Solid Interface Using the Multigrid Method - Ruchita Patel; Zulfiqar Ahmad Khan; Vasilios Bakolas; Adil Saeed (Lubricants, 2023)
Solid asperity interactions are common and inevitable under severe loading conditions for any lubricated contact. Heavy-duty machine components (gears, bearings, etc.) generally operate under Mixed Lubrication (ML), where uneven surface features contact each other when the generated fluid pressure is not enough to support the external load. The Reynolds equation is commonly used to simulate smooth lubricated contacts numerically. In rough lubricated interfaces where opposite surface asperities make contact, the Reynolds equation alone cannot accurately predict pressure using the traditional numerical simulation method. In this paper, lubrication–contact interface conditions (LCICs) have been implemented and extended to solve the multiple asperity contact problem using the full-multigrid approach. The developed novel algorithm has significantly accelerated the solution process and improved the accuracy and efficiency of pressure calculation for fluid–solid sub-interactions that can occur in ML regions. The results of the finite difference method (FDM) results have been compared with those of computational fluid dynamics (CFD) simulation to validate the newly developed model. Hence, the proposed optimized solution method will provide valuable insight to researchers and industry engineers interested in simulating the ML problem where the effect of the fluid–solid interface can be captured effectively to improve reliability in the calculation of the life expectancy of the lubricated parts.